👤

(10-4x-2)-(3+6x-2x2​

Sagot :

Answer:

Changes made to your input should not affect the solution:

(1): "x2"   was replaced by   "x^2".  1 more similar replacement(s).

STEP

1

:

Equation at the end of step 1

 ((((10-4x)-(2•(x2)))-3)+6x)-2x2

STEP  

2

:

Equation at the end of step

2

:

 ((((10 - 4x) -  2x2) -  3) +  6x) -  2x2

STEP

3

:

Trying to factor by splitting the middle term

3.1     Factoring  -4x2+2x+7  

The first term is,  -4x2  its coefficient is  -4 .

The middle term is,  +2x  its coefficient is  2 .

The last term, "the constant", is  +7  

Step-1 : Multiply the coefficient of the first term by the constant   -4 • 7 = -28  

Step-2 : Find two factors of  -28  whose sum equals the coefficient of the middle term, which is   2 .

     -28    +    1    =    -27  

     -14    +    2    =    -12  

     -7    +    4    =    -3  

     -4    +    7    =    3  

     -2    +    14    =    12  

     -1    +    28    =    27  

Answer:-4x2 + 2x + 7